VEGF (Vascular Endothelial Growth Factor) Induces NRP1 (Neuropilin-1) Cleavage via ADAMs (a Disintegrin and Metalloproteinase) 9 and 10 to Generate Novel Carboxy-Terminal NRP1 Fragments That Regulate Angiogenic Signaling. Issue 8 (August 2018) - Mehta, Vedanta; Fields, Laura; Evans, Ian M.; Yamaji, Maiko; Pellet-Many, Caroline; Jones, Timothy; Mahmoud, Marwa; Zachary, Ian
Abstract : Objective—: NRP1(neuropilin-1) acts as a coreceptor for VEGF (vascular endothelial growth factor) with an essential role in angiogenesis. Recent findings suggest that posttranslational proteolytic cleavage of VEGF receptors may be an important mechanism for regulating angiogenesis, but the role of NRP1 proteolysis and the NRP1 species generated by cleavage in endothelial cells is not known. Here, we characterize NRP1 proteolytic cleavage in endothelial cells, determine the mechanism, and investigate the role of NRP1 cleavage in regulation of endothelial cell function. Approach and Results—: NRP1 species comprising the carboxy (C)-terminal and transmembrane NRP1 domains but lacking the ligand-binding A and B regions are constitutively expressed in endothelial cells. Generation of these C-terminal domain NRP1 proteins is upregulated by phorbol ester and Ca 2+ ionophore, and reduced by pharmacological inhibition of metalloproteinases, by small interfering RNA-mediated knockdown of 2 members of ADAM (a disintegrin and metalloproteinase) family, ADAMs 9 and 10, and by a specific ADAM10 inhibitor. Furthermore, VEGF upregulates expression of these NRP1 species in an ADAM9/10-dependent manner. Transduction of endothelial cells with adenoviral constructs expressing NRP1 C-terminal domain fragments inhibited VEGF-induced phosphorylation of VEGFR2 (VEGF receptor tyrosine kinase)/KDR (kinase domain insert receptor) and decreased VEGF-stimulated endothelial cell motility and angiogenesis in coculture and aortic ring sprouting assays. Conclusions—: These findings identify novel NRP1 species in endothelial cells and demonstrate that regulation of NRP1 proteolysis via ADAMs 9 and 10 is a new regulatory pathway able to modulate VEGF angiogenic signaling. Abstract : Supplemental Digital Content is available in the text.